STRATEGIES FOR USING AUGMENTED REALITY-BASED INTERACTIVE LEARNING MEDIA TO IMPROVE THE UNDERSTANDING OF IPAS CONCEPTS - Septiani, Elviana Yustika; Soliha, Imro Atus; Yulina Fadilah (Al-Mubin, 2025)
This study aims to explore the strategy of using Augmented Reality (AR)-based interactive learning media in improving the understanding of Natural and Social Sciences (IPAS) concepts in grade V students at MI Miftahul Ulum Kanigaran. The method used was a qualitative case study with participants consisting of one experienced AR user teacher and eight students selected through purposive sampling. Data were collected through semi-structured interviews, participatory observations, and focus group discussions, then analyzed inducively following a cycle of data reduction, presentation, and verification. The results show that AR acts as a conceptual bridge that facilitates multisensory meaning, so that misconceptions of IPAS concepts can be minimized through three-dimensional visualization and instant feedback. An effective strategy includes three stages: (1) integrated planning, where teachers align AR modules with students' learning needs; (2) collaborative implementation, optimizing group discussions based on AR experience; and (3) structured reflection through the presentation of findings and peer feedback. Nonetheless, device and internet connection limitations and instructional design challenges are obstacles that require managerial support and ongoing training. This study concludes that the integration of AR with a targeted strategy and adequate infrastructure support can drive pedagogical transformation towards 21st century science learning in madrasah ibtidaiyah